Lorien Legacies Reborn: Return to Zero - Book 3 - Lore, Pittacus (New York, NY Harper, an imprint of HarperCollinsPublishers, 2019)
"When the United Nations takes drastic measures against the Human Garde to keep them in check, the students at the Academy must go on the offensive while those who have defected face off against a new and equally dangerous threat"--
Keywords: Ability -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Ability -- Fiction; Extraterrestrial beings -- Fiction; Science fiction; Science fiction